Simulations of Miocene Antarctic ice-sheet variability under increased precipitation and sub-shelf melt, using the ice-sheet model IMAU-ICE ... - Stap, Lennert B.; Hou, Suning; Bijl, Peter K. (Zenodo, 2023)
To demonstrate the viability of a precipitation regime change leading to a fundamentally different volume-to-area ratio of the Antarctic ice sheet, we deploy the 3D thermodynamical ice sheet/shelf model IMAU-ICE v1.1.1. In the standard set-up (Stap et al., 2021a, 2021b), climate forcing follows from pre-run warm and cold snapshot climate simulations. The applied climate forcing is transiently calculated based on the prescribed CO2 concentration and the modelled ice sheet size, through a matrix interpolation method. Equilibrium experiments are performed at various CO2 levels between preindustrial and 3x preindustrial CO2 values, with insolation at present-day levels and initiated from an ice-free Miocene Antarctic topography (dataset Hochmuth et al., 2020). Here, we perform additional sensitivity experiments, in which we apply a fixed precipitation increase and extreme sub-shelf melt rates. The precipitation anomaly is calculated as 25% of the warm snapshot precipitation fields, sub-shelf melt rates are set ... : L.B. Stap is funded by the Dutch Research Council (NWO), through VENI grant VI.Veni.202.031. Simulations were performed on the Gemini computing cluster of the Faculty of Science, Utrecht University. ...